A TWO-STAGE GROUP SAMPLING PLAN BASED ON TRUNCATED LIFE TESTS FOR A EXPONENTIATED FRÉCHET DISTRIBUTION - Rao, G. Srinivasa; Rosaiah, K.; Babu, M. Sridhar; Kumar, D.C.U. Siva (European Scientific Journal, ESJ, 2014)
A two-stage group acceptance sampling plan is proposed for truncated life tests when the life time of an item follows exponentiated Fréchet distribution. The decision about the lot acceptance can be made in the first or second stage according to the number of failures from each group. In this paper, we determined number of groups required for each of two stages for the underlying lifetime distribution so as to minimize the average sample number under the constraints of satisfying the producer’s and consumer’s risks simultaneously. Single-stage group sampling plans are also considered as special cases of the proposed plan and compared with the proposed plan in terms of the average sample number and the operating characteristics.